2009
DOI: 10.4161/psb.4.3.7799
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in the localization of oil body-associated signaling molecules during lipolysis in oilseeds

Abstract: Prior to and/or accompanying lipolytic degradation of triacylglycerols (TAGs) during seed germination in oilseeds, certain enzymatic and non-enzymatic signaling molecules are expressed on the oil body membranes. These include certain proteases, lipoxygenase, phospholipase A(2) and lipase. Although enough biochemical investigations have demonstrated their activities, recent developments in the in situ localization of these signaling molecules in germinating oilseeds, have enhanced our understanding in this fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 53 publications
1
22
0
Order By: Relevance
“…20 Significant transient biomolecular changes have been reported in the recent past on oil body membranes in the cells of seedling cotyledons of oilseeds, accompanying lipolysis. 31,32 All these earlier findings from the other workers and the present observations on the preferential accumulation of PAA-binding putative calcium channels on/around the oil bodies point towards the expression simply showed very faint green fluorescence upon excitation (Fig. 2I and L).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…20 Significant transient biomolecular changes have been reported in the recent past on oil body membranes in the cells of seedling cotyledons of oilseeds, accompanying lipolysis. 31,32 All these earlier findings from the other workers and the present observations on the preferential accumulation of PAA-binding putative calcium channels on/around the oil bodies point towards the expression simply showed very faint green fluorescence upon excitation (Fig. 2I and L).…”
Section: Resultssupporting
confidence: 86%
“…EGTA, a calcium-chelating agent, is routinely used to establish the involvement of calcium ions in various physiological processes. [22][23][24][25][26][27][28][29][30][31][32][33][34][35] It forms stable, water-soluble complexes with calcium ions, thereby blocking their passage across plasma membrane into the cell. 24 Safadi et al 25 reported the presence of a calcium-dependent proteinase (CDP) activity in the roots of Arabidopsis, using in gel assays.…”
Section: Resultsmentioning
confidence: 99%
“…Lipid reserve mobilization accompanying extension growth of the seedlings is also likely to exhibit photomodulation. Within the cells of seedling cotyledons, a transient expression of various enzymes (such as proteases) has been reported on the oil body membrane leading to various signaling events and disruption of OB membrane to provide access to lipase action on TAG matrix (Sadeghipour and Bhatla 2002;Vandana and Bhatla 2006;Bhatla et al 2009). Additionally, oil body constituents are also likely to get modified through the action of enzymes like LOX.…”
Section: Discussionmentioning
confidence: 98%
“…Nile red, a fluorescent probe for neutral lipids, serves as an ideal agent to monitor spatial and temporal changes in intracellular neutral lipid accumulation sites (Bhatla et al 2009;Greenspan et al 1985). Nile red fluorescing molecules accumulated as early as during late globular stage of embryo development in sunflower (Fig.…”
Section: Spatial Distribution Of Neutral Lipidsmentioning
confidence: 99%